2020
DOI: 10.3389/fbioe.2020.00293
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Engineering of Filamentous Fungi for Efficient Protein Expression and Secretion

Abstract: Filamentous fungi are considered as unique cell factories for protein production due to the high efficiency of protein secretion and superior capability of post-translational modifications. In this review, we firstly introduce the secretory pathway in filamentous fungi. We next summarize the current state-of-the-art works regarding how various genetic engineering strategies are applied for enhancing protein expression and secretion in filamentous fungi. Finally, in a future perspective, we discuss the great po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
62
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(69 citation statements)
references
References 73 publications
4
62
0
3
Order By: Relevance
“…Data obtained here showed that expression of chimeric protein in lower temperature (25-26 o C) and adding 40% more YNB culture medium into the main culture medium (BMY) was more e cient approach for protein expression than prevailing approaches such as stated in Invitrogen protocol (Safder et al .2018). It might be due to the positive effect of low temperature and nutritional supplementation on protein expression and could be considered for large-scale heterogeneous protein performance (Silverman et al2017;Mori et al 2017;Wang et al .2020) One of the major challenges in producing bio-adhesives from mussel foot proteinosis is adhesive proteins demonstrating resistance at a particular pH. In the present study, AFM microscopic images also show greater cohesion of proteins in acidic pH.…”
Section: Discussionsupporting
confidence: 54%
“…Data obtained here showed that expression of chimeric protein in lower temperature (25-26 o C) and adding 40% more YNB culture medium into the main culture medium (BMY) was more e cient approach for protein expression than prevailing approaches such as stated in Invitrogen protocol (Safder et al .2018). It might be due to the positive effect of low temperature and nutritional supplementation on protein expression and could be considered for large-scale heterogeneous protein performance (Silverman et al2017;Mori et al 2017;Wang et al .2020) One of the major challenges in producing bio-adhesives from mussel foot proteinosis is adhesive proteins demonstrating resistance at a particular pH. In the present study, AFM microscopic images also show greater cohesion of proteins in acidic pH.…”
Section: Discussionsupporting
confidence: 54%
“…In general, secretory systems are advantageous because the protein product is exported into the medium allowing for economic and straightforward downstream processing workflows [ 8 ]. Due to their extraordinary secretion capacities and inexpensive cultivation, fungal expression hosts are promising candidates for novel platforms and already the preferred hosts for the production of proteases and other hydrolytic enzymes [ 9 , 10 ]. However, the synthesis of heterologous proteins still imposes major challenges in fungal expression hosts [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Filamentous fungi are the only microorganisms that can fully degrade renewable lignocellulosic biomass and sustainably transform it into food, feed, chemicals, fuels, commodities, textiles, composite materials, antibiotics, and other drugs (Meyer et al, 2020). Their ability to perform complex posttranslational modifications (Wang et al, 2020), their greatly expanded natural protein secretion apparatus (Ward, 2012), and the enormous potential of the secondary metabolome to produce bioactive molecules (Brakhage, 2013; Keller, 2019; Nielsen et al, 2017) make filamentous fungi a favorable host for many applications (Wösten, 2019).…”
Section: Introductionmentioning
confidence: 99%